2019
DOI: 10.15359/revmar.11-2.4
|View full text |Cite
|
Sign up to set email alerts
|

Fuentes terrestres de contaminación que impactan la zona marino-costera del Golfo de Papagayo, Costa Rica

Abstract: El Golfo de Papagayo, en los últimos años, ha experimentado un acelerado desarrollo socioeconómico que puede ejercer presión sobre sus espacios y recursos naturales, y contribuir, así, al deterioro de su zona marino-costera. Por lo tanto, el objetivo de este estudio fue identificar las principales fuentes terrestres de contaminación que puedan ejercer efectos negativos sobre el ambiente y la calidad higiénico-sanitaria de las aguas de sus playas. Para recolectar información sobre la producción y el manejo de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…In a semi-closed bay with little waves, they can cause substances to remain in the aquatic environment for a longer time. Furthermore, in the surroundings of this bay, there are human populations settlements, and a large number of tourist activities are developed in the land area [14], as well as different nautical and fishing activities that make this area have high environmental fragility [3]. It is important to indicate that all these activities lead to an increase in organic matter and nutrients that, together with the autochthonous contributions, could favor eutrophication processes.…”
Section: Variability Of the Environmental Variables Analyzed Between October 2016 And February 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…In a semi-closed bay with little waves, they can cause substances to remain in the aquatic environment for a longer time. Furthermore, in the surroundings of this bay, there are human populations settlements, and a large number of tourist activities are developed in the land area [14], as well as different nautical and fishing activities that make this area have high environmental fragility [3]. It is important to indicate that all these activities lead to an increase in organic matter and nutrients that, together with the autochthonous contributions, could favor eutrophication processes.…”
Section: Variability Of the Environmental Variables Analyzed Between October 2016 And February 2018mentioning
confidence: 99%
“…In this area, some studies have been carried out on the structure of the phytoplankton community [7], its marine biodiversity [8], the reefs [9], changes in the cover of mangroves [10], temperature, salinity, and dissolved oxygen [11], as well as aspects related to climate and subsurface temperature of the sea [12]. In Culebra Bay, there is a drastic decrease in the percentages of living coral cover, the richness indices, and the diversity of species [13], which may be related to that indicated by Saravia-Arguedas et al [14], who reported hygienic-sanitary quality for some beaches in the Gulf of Papagayo located in this bay, ranging from excellent to good for the dry season and from excellent to fair for the rainy season, showing susceptible areas to deterioration in water quality. A limited number of studies related to the environmental quality of the waters of the marine-coastal area of the Gulf of Papagayo are available.…”
Section: Introductionmentioning
confidence: 95%